Use of a Hotplate at 80°C for 3 minutes to help Fixation of Histological Preparations - Burhannudin; Herbyananda, Arnando Daffa (Biomedika, 2024)
Fixation is a complex stage and requires a long time. The microwave heating process has been proven to accelerate the fixation rate, but the use of a hotplate in helping the fixation process has yet to be discovered. The study aims to determine the optimal time of 80°C hotplate heating in helping fixation. The study was conducted experimentally using a post-test only control group design. A total of 75 histological slides of hepatic tissue of male Wistar rats were divided into five groups with equal size: control group (conventional/K and microwave/M) and three treatments of 80°C hotplate for 3 minutes (H1), 5 minutes (H2) and 10 minutes (H3). Hematoxylin Eosin (HE) staining results of all histology slides were morphologically observed and scored based on previous studies. In addition, the staining scores were tested for differences between groups using the Kruskal-Wallis and Mann-Whitney tests, with p values <0.05 being significant. The results of morphological observations of HE stains stated that the median H2 group was worth a score of 3, while the other groups were worth a score of 2. The results of the Kruskal-Wallis and Mann-Whitney tests showed that the H2 group significantly differed from the control group (p<0.05). This shows that using a hotplate at 80 ° C for 5 minutes can help the fixation process in making histological preparations of rat hepatic tissue.